Battling Against COVID-19 Infodemic in Indonesia: A Sociocybernetics Perspective - Lovira Putri; Reno F. Rafly (Centre for Asian Social Science Research (CASSR), Faculty of Social and Political Sciences, UIN Sunan Gunung Djati Bandung, 2021)
As Indonesians collectively fight against the COVID-19 pandemic, the nation is simultaneously combatting the rampant spread of misinformation related to COVID-19. This phenomenon is often referred to as an ‘infodemic,’ defined by the World Health Organization (WHO) as the mass spread of information, factual or nonfactual, during a disease outbreak. In this article, we employ the methods of sociocybernetics analysis to examine the COVID-19 infodemic in Indonesia. We divide this paper into two sections. In the first section, we lay out the current state of the problem in Indonesia -how misinformation has challenged the post-pandemic recovery and changed the dynamics of Indonesian society at all levels, ranging from individuals to the society as-a-whole. In the second section, we propose a model, based on the approach of sociocybernetics, by which we propose to assess this challenge not just as a single entity but as a continuous, looping process, from the conception to the impact it has caused at all levels (micro, meso, and macro) of society. Given the complexity of this issue, we propose to develop an awareness and the education of cybernetics or systems thinking across multiple sectors when dealing with the infodemic in Indonesia.